Building Trust in E-Commerce Platform: The Effect of TAM Factor to Repurchase Intention - Tiffany, Laurensia I Gusti Ayu Carla; Sutrisno, Timotius F C W; Andrina, Anak Agung Ayu Puty (Journal of Economics and Management Scienties, 2025)
This study aims to examine how the factors in the Technology Acceptance Model (TAM), namely ease of Use, security, and privacy concerns, influence repurchase intention on the Shopee e-commerce platform, with trust as a mediator. The research targets active students at Ciputra University Surabaya who use Shopee as their primary e-commerce platform for transactions. A quantitative approach was used, with a survey design involving 304 respondents. Data were collected through a questionnaire using a 7-point Likert scale and analyzed using Structural Equation Modeling (SEM) via SmartPLS 4.0. The results show that Ease of Use, Security, and Privacy Concerns significantly influence Trust, each with values above the ideal threshold. Furthermore, Trust serves as a mediator between these TAM factors and repurchase intention. Privacy concerns proved to be the strongest factor influencing trust, highlighting the importance of data protection in building user trust. These findings indicate the importance of optimizing platform usability, implementing robust security measures, and establishing clear privacy policies to gain user trust and encourage repurchase intention.